EXPLORING TEACHER’S SCAFFOLDING TO THE STUDENTS IN TEACHING WRITING - Rohmat Kamil (Journal of English and Education, 2017)
The research entitled “Exploring Teacher’s Scaffolding to Students in Teaching Writing” is focused at investigating teacher’s ways to provide Scaffolding and challenges of implementing Scaffolding in teaching writing Descriptive text to seventh grade students in Parongpong, West Java, Indonesia. The data were collected from classroom observation, field notes, and semi-structured interview. The data obtained were transcribed and analyzed by using curriculum cycles framework (Hammond, 2001; Gibbons, 2002; Emilia, 2010). Besides, the data were also examined based on Scaffolding types theories (Roehler Cantlon, 1997; Hammond, 2001; Gibbons, 2002; Walqui, 2006).  The results revealed that six types of Scaffolding were used by the teacher in teaching writing. The most intensive Scaffolding was given in Building the Field and Modeling stage of the curriculum cycle, and all Scaffolding was reduced in the Independent Writing stage. The results also showed various ways were used by teacher to provide Scaffolding; asking previous lesson, providing illustration, explaning Grammar and text structure, giving students chance to participate in learning process, reading text model, and providing supportive and corrective feedback towards students’ responses. Furthermore, some challenges faced by teacher in using Scaffolding were the amount of students, language intruction and time constraint.